An investigation by transmission electron microscopy of freeze replicas of dog articular cartilage surfaces: the fibre-rich surface structure. - Gardner, D L (1983)
Femoral condylar cartilage blocks from the disarticulated stifle joints of five inbred beagle dogs were rapidly frozen. Single stage platinum and carbon replicas were prepared at 78 K from the unfixed, hydrated frozen material. Transmission electron microscopic investigations of the replicas were then made. Two different forms of fine cartilage surface structure were suggested by the low temperature replicas. The first, amorphous and with few fibres, was thought to represent the normal, superficial lamina obscurans. The second displayed many delicate parallel arrays of collagen fibrils with a periodic structure of 68-71 nm. Between these arrays were gently convex smooth-surfaced elevations, 150-500 nm in diameter, and therefore two orders of magnitude smaller than the tertiary surface undulations previously identified by light microscopy and by scanning electron microscopy. It is suggested that the 150-500 nm elevations seen at the replicated surface may be expanded proteoglycans, restrained laterally and deeply, less restrained superficially because of the loss, during preparation, of the lamina obscurans. Other hemispherical, replicated surface deposits 400-1700 nm in diameter are believed to be lipid.